The influence of teenagers on a family’s vacation choices - Maria Teresa Borges Tiago; Flávio Gomes Borges Tiago (Tourism & Management Studies, 2013)
Family decision-making research has frequently examined the roles of adults and children on purchase decisions. Empirical results show a propensity toward a joint decision process in problem recognition and the final decision stages. This article argues that teenagers’ influence on a family’ buying decisions suffers from a certain conceptual and definitional ambiguity, and oversimplification regarding the different modes of influence. Nevertheless, there is a consensus in business and academia that kids in general have an increasing influence in the decision making process of families. Thus, the objectives of this research are to measure teenagers’ and parents' perceptions regarding tactics used by both, especially pester power, in the context of the decision-making process for a family’s travelling choice and for breakfast cereals. The research aims to assess the differences driven by demographic characteristics.